ANALISIS DAYA DUKUNG TIANG PANCANG BERDASARKAN HASIL DATA KALENDERING PADA PROYEK JEMBATAN PILE SLAB BUKIT RAWI - Azzahra, Olivia Galuh (Universitas Lambung Mangkurat, 2023)
The construction of a pile slab bridge on the Palangka Raya-Bagugus road section was built to deal with flooding that often occurs due to overflowing water from the Kahayan river. The plan uses a pile foundation because the type of soil at that location is swamp and peat soil which has a very low bearing capacity. Soil bearing capacity can be obtained by carrying out soil investigations such as calendering investigations and PDA tests. This study aims to analyze the bearing capacity of a single pile foundation using the results of calendaring data with Danish formulas and PDA test interpretation data. Based on the results of the analysis and calculation of the carrying capacity of the single pile that occurred at point B-12-C with the results of calendaring data Qu 358,520 tons and Qa 119.507 tons, while with the results of PDA Test Qu 185.90 tons, Qs 117.7 tons and Qb 68.3 tons. The results of the analysis and calculation of the carrying capacity of a single pile that occurred at point B-12-D with the results of calendaring data Qu 501,404 tons and Qa 164,135 tons while with the results of PDA Test Qu 165.00 tons, Qs 115.8 tons and Qb 49.2 tons.